2013
DOI: 10.7243/2050-120x-2-18
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasospasm: a review of current developments in drug therapy and research

Abstract: In this manuscript a comprehensive coverage of recent developments in the drug therapy of vasospasm while providing the background information that neuroscientists need to understand its rationale. The range of new agents available for treatment of cerebral vasospasm is expanding rapidly along with rapid advances in pharmacology and physiology that are uncovering the mechanisms of this disease. Although there are many publications for treatment of cerebral vasospasm, most are focusing on different aspects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 142 publications
0
9
0
Order By: Relevance
“…The breakdown of the 40 articles was as follows: epidemiology (3), pathophysiology (9), time course (5), predictors (5), digital subtraction angiography (DSA; 4), CTA (3), CT perfusion (3), 3 electroencephalography (3), TCD ultrasonography (3), brain tissue oxygenation (1), microdialysis (2), thermal diffusion flowmetry (2), jugular bulb oximetry (2), and treatment (7) studies. The main findings are compiled in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The breakdown of the 40 articles was as follows: epidemiology (3), pathophysiology (9), time course (5), predictors (5), digital subtraction angiography (DSA; 4), CTA (3), CT perfusion (3), 3 electroencephalography (3), TCD ultrasonography (3), brain tissue oxygenation (1), microdialysis (2), thermal diffusion flowmetry (2), jugular bulb oximetry (2), and treatment (7) studies. The main findings are compiled in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…This decreases calcium influx into cells, which then decreases smooth muscle cell contractility, ultimately preventing vasospasm from occurring. 2 Although some moderately sized studies have shown that nimodipine has some benefit in reducing the incidence of vasospasm, large-scale meta-analyses have shown that differences in mortality rates were not statistically significant with the addition of nimodipine. 11 Stein and Le Roux proposed that there might be a role for nimodipine usage in a smaller subset of PTV cases as evidenced by a decreased incidence of vasospasm; however, this requires further investigation.…”
Section: Contemporary Paradigms In Management and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several medical therapies and the effect of lumbar drainage are being investigated. 2,30 Hydrocephalus Requiring a Shunt Several earlier publications have shown that chronic post-aSAH hydrocephalus is related to significant morbidity and readmission to the hospital. 1,5,12,18,29,40 Potential reasons for an impaired outcome after the need for permanent cerebrospinal fluid diversion have been discussed in a recent publication and included elevated intracranial pressure, injury from catheter misplacement, rehemorrhage, and shunt infections.…”
Section: Delayed Cerebral Vasospasm and Ischemiamentioning
confidence: 99%
“…The consequences of rupture of an aneurysm are both on the cerebral and systemic physiology leading to multi system changes (Chen et al, 2014). Despite technological advances in the management for prevention of rebleeding, the blood present in the intracranial space itself acts as a trigger for various inflammatory pathways leading to delayed cerebral ischemia and worsening the outcome of the patients or further adding to ongoing neurological insults (Archavlis andCarvi Y Nievas et al, 2013, Chaichana et al, 2010). Though the clinical spectrum of the disease has been established, mechanisms and pathophysiology of disease initiation and progression, i.e.…”
Section: Introductionmentioning
confidence: 99%